Ulama Recommendations and Political Buzzers in West Sumatra's 2024 Elections: A Fiqh Siyāsah Perspective - Miswardi; Fajrul Wadi; Elfiani; Basri Na'ali; Zaqiaty Salma; Hoirol Anuar bin Makdin (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study aims to analyze the role of recommendations from religious leaders in shaping political influence in the 2024 regional head elections in West Sumatra and to examine this phenomenon from the perspectives of hadith and contemporary political fiqh. This study employs an empirical legal research methodology using a case study approach and a juridical approach. Data were collected through interviews with religious scholars and members of the public involved in the electoral dynamics in West Sumatra. Secondary data were obtained through a literature review. Research findings on the existence of recommendations from religious scholars in the 2024 Regional Elections in West Sumatra The role of clerical endorsements in the 2024 regional elections in West Sumatra demonstrates that political legitimacy is no longer built solely through the traditional religious authority held by clerics, but is also influenced by digital actors such as influencers and online promoters. This offers a new perspective: the process of shaping public opinion in the digital sphere has become a crucial component of modern political dynamics. Therefore, the concepts of shura, amar ma’ruf nahi munkar, and the authority of religious scholars need to be re-examined in the context of digital political communication